The antitumor activity of tumor-homing peptide-modified thermosensitive liposomes containing doxorubicin on MCF-7/ADR: in vitro and in vivo - Wang, Chao (Int J Nanomedicine, 2015)
Clotted plasma proteins are present on the walls of tumor vessels and in tumor stroma. Tumor-homing peptide Cys-Arg-Glu-Lys-Ala (CREKA) could recognize the clotted plasma proteins in tumor vessels. Thermosensitive liposomes could immediately release the encapsulated drug in the vasculature of the heated tumor. In this study, we designed a novel form of targeted thermosensitive liposomes, CREKA-modified lysolipid-containing thermosensitive liposomes (LTSLs), containing doxorubicin (DOX) (DOX-LTSL-CREKA), to investigate the hypothesis that DOX-LTSL-CREKA might target the clotted plasma proteins in tumor vessels as well as tumor stroma and then exhibit burst release of the encapsulated DOX at the heated tumor site. We also hypothesized that the high local drug concentration produced by these thermosensitive liposomes after local hyperthermia treatment will be useful for treatment of multidrug resistance. The multidrug-resistant human breast adenocarcinoma (MCF-7/ADR) cell line was chosen as a tumor cell model, and the targeting and immediate release characteristics of DOX-LTSL-CREKA were investigated in vitro and in vivo. Furthermore, the antitumor activity of DOX-LTSL-CREKA was evaluated in MCF-7/ADR tumor-bearing nude mice in vivo. The targeting effect of the CREKA-modified thermosensitive liposomes on the clotted plasma proteins was confirmed in our in vivo imaging and immunohistochemistry experiments. The burst release of this delivery system was observed in our in vitro temperature-triggered DOX release and flow cytometry analysis and also by confocal microscopy experiments. The antitumor activity of the DOX-LTSL-CREKA was confirmed in tumor-bearing nude mice in vivo. Our findings suggest that the combination of targeting the clotted plasma proteins in the tumor vessel wall as well as tumor stroma by using CREKA peptide and temperature-triggered drug release from liposomes by using thermosensitive liposomes offers an attractive strategy for chemotherapeutic drug delivery to tumors.